1998
DOI: 10.1063/1.367793
|View full text |Cite
|
Sign up to set email alerts
|

Colossal magnetoresistance in La1−xLixMnO3

Abstract: La 1−x Li x MnO 3 (x=0, 0.1, 0.2, and 0.3) were synthesized by using conventional solid state reaction and partial melting technique. The compounds were determined to be of rhombohedral structure by x-ray powder diffraction. For the x=0.2 and x=0.3 samples, room temperature neutron powder diffraction patterns were collected and analyzed with the Rietveld method. The analysis showed that the Li substitutes onto the La site in the rhombohedral perovskite lattice. Resistivities were measured between 4.2 K and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…They argued that smaller size of Li 1+ (0.78Å) is responsible for the peculiar behaviour of resistivity. Bhattacharya et al [25] noticed a decrease in T C and T P with Li doping in La 0.7 Ca 0.3−y Li y MnO 3 and their findings were similar to that of Wang et al [24]. Roy et al [26] reported the behaviour of Na 1+ doped La 1−x Na x MnO 3 (0.07 < x < 0.20).…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…They argued that smaller size of Li 1+ (0.78Å) is responsible for the peculiar behaviour of resistivity. Bhattacharya et al [25] noticed a decrease in T C and T P with Li doping in La 0.7 Ca 0.3−y Li y MnO 3 and their findings were similar to that of Wang et al [24]. Roy et al [26] reported the behaviour of Na 1+ doped La 1−x Na x MnO 3 (0.07 < x < 0.20).…”
Section: Introductionsupporting
confidence: 64%
“…So far, most of the studies have been focused towards the divalent alkaline-earth ion doped compounds. In contrast, there are few reports on the studies of monovalent alkali-metal doped samples [23][24][25][26][27][28][29][30][31]. These compounds were synthesized many years ago and tested as oxidation catalysts for exhausts gases for the internal combustion engines [32].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The sample exhibited a special transport behavior [7,8], it shows that there were double peaks or shoulder in the temperature dependence of resistivity measurement. This phenomenon was initially explained by a possible phase inhomogeneity in La 1Àx A x MnO 3 (A=K, Na) sample due to their sintering in short time [9,10]. However, the second resistivity peak could not be removed no matter what synthesis techniques was used, either by preparing the bulk sample in a long sintering time or making thin film [9][10][11].…”
Section: Introductionmentioning
confidence: 97%
“…However, monovalent cations, such as Li were seldom investigated as dopants of LaMnO 3 [4][5][6][7][8][9][10]. Therefore, in this study, various amounts of Li ions were substituted for La in LaMnO 3 using a solid state reaction method.…”
Section: Introductionmentioning
confidence: 99%